Fatigue characterization of mechanical components in service - G. Fargione; D. Tringale; E. Guglielmino; G. Risitano (Fracture and Structural Integrity)
The quickly identify of fatigue limit of a mechanical component with good approximation is currently a significant practical problem not yet resolved in a satisfactory way. Generally, for a mechanical component, the fatigue strength reduction factor (i) is difficult to evaluate especially when it is in service.In this paper, the procedures for crack paths individuation and consequently damage evaluation (adopted in laboratory for stressed specimens with planned load histories) are applied to mechanical components, already failed during service. The energy parameters, proposed by the authors for the evaluation of the fatigue behavior of the materials [1-5], are defined on specimens derived from a flange bolts. The flange connecting pipes at high temperature and pressure. Due to the loss of the seal, the bolts have been subjected to a hot flow steam addition to the normal stress.The numerical analysis coupled experimental analysis (measurement of surface temperature during static and dynamic tests of specimens taken from damaged tie rods), has helped to determine the causes of failure of the tie rods.The determination of an energy parameter for the evaluation of the damage showed that factors related to the heat release of the material (loaded) may also help to understand the causes of failure of mechanical components.